Application of blockchain in urban rail traffic edge computing network - Gaochang XIE; Hua LU; Qinqin TANG; Han ZHU; Chenghao LIANG; Wen WEN; Renchao XIE (Dianxin kexue)
Multi-access edge computing (MEC) can provide high-quality service capabilities for computing-intensive services and delay-sensitive services in urban rail traffic.However, many edge facilities in rail traffic edge computing network are exposed to an open environment, and their privacy protection and transmission security are facing great challenges.Blockchain has functional characteristics such as distributed ledger, consensus mechanism, smart contract, and decentralized application.Therefore, the use of blockchain can build a systematic security protection mechanism for the distributed rail traffic edge computing network to ensure network security and data security and realize high-quality urban rail traffic services.Firstly, the basic concept of the blockchain and the urban rail traffic edge computing network architecture were introduced.Then, the structure and application content of the rail traffic edge computing network security protection mechanism integrated with the blockchain was discussed in detail.Finally, the open research issues and challenges of the security protection mechanism were analyzed.